Implikasi Pendaftaran Tanah Sistematis Lengkap (PTSL) Sebagai Upaya Pencegahan Konflik Sengketa Tanah di Kecamatan Batang Kuis - Yunita Permata Sari Siregar; Adlin Budhiawan (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Today, land disputes not only involve neighboring groups and other parties, but also involve confrontations with various federal authorities. North Sumatra Province is the second province in Indonesia most affected by land disputes, according to Hadi Tjahjanto, Minister of Land Affairs. East Java is the province that has the largest number of land disputes, so North Sumatra Province is the second most affected province. In 2020, there were five land disputes which were considered to be hampering development in North Sumatra. The land disputes include: Former PTPN II HGU covering an area of ​​5,8738 hectares; HGU Number 171/Simalingkar; HGU Number 92/Sei Mencirim; Land Conflict in Sarirejo; and construction of a sports arena which was previously still on land occupied by HGU PTPN II before it was built in Batang Kuis District. A descriptive approach was taken in the research conducted here. When referring to research, the words “descriptive research” refer to research that attempts to describe the conclusions of an investigation. The aim of this type of descriptive research is to provide an explanation, description and validation of the phenomenon being investigated. The research results show that in Batang Kuis District, the Systematic Land Registration Mechanism (PTSL) is implemented as a whole. Land registration in Indonesia is a form of land registration "Cadaster Rechts", namely a form of land registration that seeks to provide legal certainty and protection for holders of land rights. The interpretation of this land registration is in accordance with the provisions contained in Article 19 of the UUPA.